Efficacy of Pregabalin and Duloxetine in Patients with Painful Diabetic Peripheral Neuropathy (PDPN): A Multi-Centre Phase IV Clinical Trial-BLOSSOM - Martin Rakusa; Iris Marolt; Zorica Stevic; Sandra Vuckovic Rebrina; Tatjana Milenkovic; Adam Stepien (MDPI AG, 2023)
Introduction: Our trial (ClinicalTrials.gov Identifier: NCT04246619) evaluates the efficacy of two generic medications, pregabalin and duloxetine, for treating pain in PDPN patients. Methods: The patients were randomised either into the pregabalin (99) or the duloxetine (102) arm. Pain was evaluated using the DN-4 questionnaire, and visual analogue scales (VASs, 0-100 mm) were used to measure the average pain intensity (API), worst pain intensity (WPI) in the last 24 h and current pain intensity (CPI). Results: The proportion of patients with a clinically significant improvement in the API at Week 12 was 88.3% [CI 81.7%, 94.8%] in the pregabalin arm and 86.9% [CI 76.7%, 97.1%] in the duloxetine arm. After 12 weeks, the CPI, API, and WPI decreased by −35.3 [−40.5, −30.0], −37.0 [−41.4, −32.6], and −41.6 [−46.6, −36.5] in the pregabalin arm, and by −35.0 [−39.2, −30.7], −36.9 [−41.5, −32.3], and −40.0 [−44.8, −35.2] in the duloxetine arm (all in mm, all p < 0.001). Conclusion: Our results demonstrate that pregabalin and duloxetine are effective medications for treating pain in PDPN in more than 86% of all randomised patients.